Evidence of Burkholderia pseudomallei-Specific Immunity in Patient Sera Persistently Nonreactive by the Indirect Hemagglutination Assay - Harris, Patrick N. A. (American Society for Microbiology, 2011)
The indirect hemagglutination assay (IHA) is the most frequently used serological test to confirm exposure to Burkholderia pseudomallei. Patients with culture-confirmed disease often have a nonreactive IHA at presentation and occasionally fail to seroconvert on serial testing. We investigated whether using antigens derived from the cultured isolates of persistently IHA-nonreactive patient sera improved the sensitivity of the IHA. In addition, we assessed the antigen-specific lymphocyte response in this group of patients to a panel of B. pseudomallei antigens, including those derived from their own cultured isolates. Eleven patients with culture-proven melioidosis were identified as having persistently IHA-nonreactive sera. A modified IHA using erythrocytes sensitized with patient isolate-derived antigen tested against convalescent-phase serum was performed. The majority (82%) of sera showed a negative (≤1:5) result, one was borderline (1:20), and one was positive at the cutoff value (1:40). IHA-nonreactive sera were also tested by enzyme immunoassay (EIA), with 73% (8/11) demonstrating IgG positivity. In addition, lymphocytes isolated from persistently IHA-nonreactive patient sera demonstrated significantly increased proliferation in response to B. pseudomallei antigens compared to controls. These studies demonstrate the presence of B. pseudomallei-specific antibody by EIA and B. pseudomallei-specific lymphocytes in patient sera categorized as persistently nonreactive according to the IHA. New immunoassays are required and should incorporate B. pseudomallei antigens that are immunoreactive for this subset of IHA-nonreactive patient sera.